2009
DOI: 10.1017/s1368980008003315
|View full text |Cite
|
Sign up to set email alerts
|

Iodine deficiency in pregnant women in eastern Turkey (Malatya Province): 7 years after the introduction of mandatory table salt iodization

Abstract: ObjectiveThe aim of the present study was to evaluate the urinary I excretion of pregnant women in Malatya Province, eastern Turkey.Design and settingA cross-sectional study was performed on pregnant women in urban and rural settlements of Malatya Province.SubjectsUrinary I excretion was measured for 824 pregnant women who were randomly selected using a probability-proportional-to-size sampling methodology.ResultsMedian urinary I concentration (UIC) of pregnant women was 77·4 μg/l. The percentage of pregnant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 15 publications
2
26
1
Order By: Relevance
“…More importantly, 72·8% of these pregnant women were iodine deficient and 15·4% had goitre. Therefore, our results demonstrate that iodine deficiency remains a serious problem for pregnant women living in Ankara, an area that appeared to be iodine sufficient in previous studies, and are in agreement with similar reports of low iodine status in pregnant women from other regions of Turkey . Our results also indicate that iodine nutritional status among SAC does not reflect the iodine supply of pregnant women and their offspring in the same region.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…More importantly, 72·8% of these pregnant women were iodine deficient and 15·4% had goitre. Therefore, our results demonstrate that iodine deficiency remains a serious problem for pregnant women living in Ankara, an area that appeared to be iodine sufficient in previous studies, and are in agreement with similar reports of low iodine status in pregnant women from other regions of Turkey . Our results also indicate that iodine nutritional status among SAC does not reflect the iodine supply of pregnant women and their offspring in the same region.…”
Section: Discussionmentioning
confidence: 54%
“…Even though the large data set of national CH screening in Turkey has not yet been published, the current regional data showing a high prevalence of neonates with elevated TSH levels implies the presence of inadequate iodine nutrition of pregnant women . The present and other studies, therefore, provide direct evidence for the problem of iodine deficiency among pregnant women in Turkey.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Iodine deficiency in the mothers, despite the fact that almost all of them had used iodized salt during pregnancy, showed that the use of iodized salt during pregnancy and nursing periods did not meet their iodine requirements. Even though the use of iodized salt has become mandatory in Turkey since the initiation of the national program in 1998, studies have shown that the rate of iodine deficiency continued to be significantly high in sensitive populations, such as pregnant and nursing mothers (11,12,13,14). The iodine requirement increases in pregnant and nursing mothers and cannot be satisfied by using standard iodized salts.…”
Section: Discussionmentioning
confidence: 99%